Creating Business Value through IoT-Based Waste Management Web Dashboard - Wilda Susanti; Nicholas Renaldo; Achmad Tavip Junaedi; Mukhsin Mukhsin; Johan Johan; Yulvia Nora Marlim; Gusrio Tendra; Wahyu Joni Kurniawan; Fauzan Azim (Luxury: Landscape of Business Administration, 2026)
The rapid growth of urbanization and industrial activities has increased the complexity of waste management operations within business organizations, leading to rising costs and managerial challenges. While the Internet of Things (IoT) has enabled real-time data collection in waste management, business value creation depends on how such data are integrated into managerial information systems. This study aims to develop and evaluate an IoT-based waste management web dashboard that supports operational monitoring and managerial decision-making to create business value. Using a Design Science Research (DSR) methodology, this study designs an integrated system that collects real-time waste volume data through IoT-enabled sensors and presents the information via a centralized web dashboard. The system is evaluated using a mixed approach combining operational performance indicators and user perceptions based on Information Systems Success Theory. The results indicate improvements in operational efficiency, resource allocation, and decision-making quality following system implementation. The findings demonstrate that the proposed web dashboard functions as a strategic managerial information system rather than a purely technical solution. By enhancing information quality and managerial control, the system contributes to business value creation through improved operational performance and supports digital transformation and sustainability-oriented business practices. This study contributes to the business and management literature by shifting the focus of IoT-based waste management research from technical performance to managerial relevance and value creation.